Outcome of Post Esophageal Variceal Band Ligation with Sucralfate and Proton Pump Inhibitor vs. Proton Pump Inhibitor Alone in Cirrhotic Patients - Karki, Binod; Shrestha, Ramila; Paudel, Bidhan Nidhi; KC, Sudhamshu; Khadka, Dibas; Thapa, Suresh; Purbey, Bibek Kumar; Karki, Sanjit; Thapa, Pukar; Mandal, Amrendra (Nepalese Medical Journal, 2019)
Introduction: Endoscopic band ligation is the mainstay of treatment in bleeding varices in cirrhosis. Subsequent bleeding from the band ulcers is a possible complication. Proton pump inhibitors and Sucralfate are commonly used post band ligation and often in combination. The aim of the study was to identify the advantage of combining Sucralfate to proton pump inhibitor in reducing the number and size of band ulcers. Materials and Methods: This was an open-label comparative study conducted in a tertiary level hospital of Nepal. Patients with cirrhosis after band ligation were included. Eligible patients were randomized into a proton pump inhibitor alone (Group A) or proton pump inhibitor and sucralfate group (Group B) and they underwent upper gastrointestinal endoscopy after two weeks. Baseline parameters, number and mean size of band ulcers were compared. Results: A total of 58 patients, 29 in each group, were evaluated. The baseline characteristics were comparable. EBL was done for bleeding varices in 51.7% and as primary prophylaxis in the rest of them. All the patients had band ulcers after two weeks. The mean size of the largest ulcer was 1.62±0.72 and 1.10±0.60 (p=0.78) respectively in groups A and B. Low albumin was significantly associated with OR of 8.7 (95% CI:1.68-44.99) for the formation of multiple (more than two) ulcers (p=0.01). Conclusions: The ulcer formation was universal after band application. The addition of sucralfate did not offer more benefits in terms of the number and mean size of the ulcer. Low albumin was the independent predictor for multiple ulcer formation.